PERANCANGAN SISTEM PENUNJANG KEPUTUSAN PENENTU PROGRAM STUDI DI PERGURUAN TINGGI DENGAN METODE KUDER PREFERENCE RECORD - Aditya Tanuwijaya; Dedi Trisnawarman; Wasino Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
The study program goal for student is to make them can focus more on developing their abilities and interests that they have, but it is difficult when the student misdirects. The Solution is a Decision Support System using Kuder Preference Record method and Simple Additive Weighting method to find priority for decision making. The result from the test is the decision support system can assist in determining which study programs are of interest to students based on ranking